Broadband short term X‐ray variability of the quasar PDS 456. Issue 4 (May 2016) - Matzeu, G. A.; Reeves, J. N.; Nardini, E.; Braito, V.; Costa, M. T.; Tombesi, F.; Gofford, J.
Abstract: We present a detailed analysis of a recent 500 ks net exposure Suzaku observation, carried out in 2013, of the nearby ( z = 0.184) luminous ( L bol ∼ 10 47 erg s –1 ) quasar PDS 456 in which the X‐ray flux was unusually low. The short term X‐ray spectral variability has been interpreted in terms of variable absorption and/or intrinsic continuum changes. In the former scenario, the spectral variability is due to variable covering factors of two regions of partially covering absorbers. We find that these absorbers are characterised by an outflow velocity comparable to that of the highly ionised wind, i.e. ∼ 0.25 c, at the 99.9% (3.26σ) confidence level. This suggests that the partially absorbing clouds may be the denser clumpy part of the inhomogeneous wind. Following an obscuration event we obtained a direct estimate of the size of the X‐ray emitting region, to be not larger than 20 R g in PDS 456. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)